Kualitas Sumber Daya Manusia dan Pertumbuhan Ekonomi Kalimantan - Fitrianingtyas, Winda; Nuryadin, Muhammad Rusmin (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2023)
This study shows the influence of the quality of human resources as measured by indicators of the human development index on economic growth Kalimantan. This study uses secondary data with quantitative types obtained from the Central Statistics Agency from 2013 to 2021. The data is a new method of mean years of schooling, life expectancy rate, per capita expenditure, and economic growth. This study uses panel data regression from 5 provinces in Kalimantan using classical assumption test, hypothesis testing, and coefficient determination. Partially, education level has a significant and negative effect on Kalimantan's economic growth, health has no significant and negative effect on Kalimantan's economic growth, and the economy has a significant and positive effect on Kalimantan's economic growth. Simultaneously, three independent variables significantly influence Kalimantan's economic growth. The most dominant variable is the economic variable.